Mechanical properties of high strength concrete that replace cement partly by using fly ash and eggshell powder - Teara, Ashraf; Doh, Shu Ing (Elsevier Ltd., 2020)
Global warming, climate change and greenhouse gases all these phrases are becoming an essential and significant topic to talk about in media in recent moments. One of the main and most elements that effect is carbon dioxide (CO2). Cement factories are the third higher producers of (CO2) after fossil fuels and land-use change. Cement factories emit in the atmosphere roughly about 5–7% of the total volume. Reducing the cement amount in concrete mixing is being a big challenge for researchers by replacing it with materials that are considered friendly to the environment or as waste. Possibilities of using waste materials for high strength concrete are the main aim for this research and to reduce the cement amount in concrete. Making concrete by replacing cement with green materials have been affected positively in our environment. Fly ash (FA) and eggshell powder (ESP) is the waste elements are using in this research by replacing them partly with cement in concrete mix. The percentages of replacement by weight are 5% and 10% of eggshell powder and 20%, 30%, 40% and 50% of fly ash class F. Property of all concrete mixes are tested for fresh and dried samples. Slump test, compressive strength test, flexural strength test and ultrasonic pulse velocity (UPV) had been done to all samples after curing in water until the day of test. The best results were for two mixes. The mixes 5% ESP with 30% FA and 5% ESP with 40% FA got the highest results compared to other mixes. 58.9 MPa and 56 MPa are the results for compressive strength, respectively. Replacing cement with green materials is possible to make high strength concrete and reducing the use of cement up to 45% in weight.